PERAN BUMDES MUARA GEMILAG DALAM MENINGKATAKAN EKONOMI MASYARAKAT DI DESA BATUYANG KECAMATAN PRINGGABAYA KABUPATEN LOMBOK TIMUR - Alviani; Muhammad Syayuti; Baiq Rizka Milania Ulpah; Mimi Cahyani; Lale Ajeng Khalifatun Wardani (Fakultas Ekonomi dan Bisnis Universitas Islam Al-Azhar Mataram, 2024)
This research is entitlend “The Role of BUMDES Muara Gemilang in improving the community economy in Batuyang village, Pringgabaya Diatrict, East Lombok Regency”. The aim of this research is to analyze the role of BUMDES Muara Gemilang in impoving the community economy in Batuyang village, Pringgabaya District, East Lombok Regency. This research is qualitative research data was obtained from interviews with the community in Batuyang Village. The results of this research indicate that the existene of BUMDES in Batuyang Village has not been able to improve the economy of the people in Batuyang Vilage.